2017
DOI: 10.1017/jpa.2016.160
|View full text |Cite
|
Sign up to set email alerts
|

First record of Toxodontidae (Mammalia, Notoungulata) from the late Miocene–early Pliocene of the southern central Andes, NW Argentina

Abstract: Abstract.-A new species of toxodontid notoungulate, Xotodon maimarensis n. sp., is described from the Maimará Formation (late Miocene-early Pliocene), Jujuy Province, northwestern Argentina. This is the first record of a toxodontid from the Eastern Cordillera. The specimen is housed at the Museo de Geología, Mineralogía y Paleontología, Instituto de Geología y Minería de la Universidad Nacional de Jujuy. It consists of an incomplete mandible preserving the right mandibular ramus with part of the dental series,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 19 publications
(47 reference statements)
0
16
0
1
Order By: Relevance
“…Macrochorobates scalabrinii has been recorded in the Andalhuala Formation, Catamarca Province (Marshall and Patterson, 1981; Bossi et al, 1987; Esteban and Nasif, 1996; Esteban et al, 2001). Radiometric dating for this unit estimated the age to be between 7.14 and 5.59 Ma (Marshall and Patterson, 1981; Latorre et al, 1997; Reguero and Candela, 2011; Bonini et al, 2017). This species has also been cited for the Epecuén Formation (Huayquerian SALMA), Buenos Aires Province (Scillato-Yané, 1980, 1982); Cerro Azul Formation (Huayquerian SALMA), La Pampa Province (Esteban et al, 2001; Urrutia et al, 2008); Salicas Formation, La Rioja Province (Tauber, 2005; Brandoni et al, 2012); and Las Flores Formation, San Juan Province (Contreras, 2007; Contreras et al, 2013) in which the fossil-bearing level is between 6.9 and 6.3 Ma (Ré et al, 2003).…”
Section: Systematic Paleontologymentioning
confidence: 99%
See 2 more Smart Citations
“…Macrochorobates scalabrinii has been recorded in the Andalhuala Formation, Catamarca Province (Marshall and Patterson, 1981; Bossi et al, 1987; Esteban and Nasif, 1996; Esteban et al, 2001). Radiometric dating for this unit estimated the age to be between 7.14 and 5.59 Ma (Marshall and Patterson, 1981; Latorre et al, 1997; Reguero and Candela, 2011; Bonini et al, 2017). This species has also been cited for the Epecuén Formation (Huayquerian SALMA), Buenos Aires Province (Scillato-Yané, 1980, 1982); Cerro Azul Formation (Huayquerian SALMA), La Pampa Province (Esteban et al, 2001; Urrutia et al, 2008); Salicas Formation, La Rioja Province (Tauber, 2005; Brandoni et al, 2012); and Las Flores Formation, San Juan Province (Contreras, 2007; Contreras et al, 2013) in which the fossil-bearing level is between 6.9 and 6.3 Ma (Ré et al, 2003).…”
Section: Systematic Paleontologymentioning
confidence: 99%
“…Most knowledge of the evolutionary history of Xenarthra comes from southern South America (Carlini et al, 2005; Croft et al, 2016), but knowledge of the group from middle and low latitudes has recently increased (Cozzuol, 2006; Ciancio et al, 2013; Tejada-Lara et al, 2015; Amson et al, 2016; Antoine et al, 2016), including Andean and sub-Andean areas (Croft et al, 2004, 2007, 2009, 2016; Reguero and Candela, 2008, 2011; Contreras et al, 2013; Bonini et al, 2017). Particularly between 30°S and 15°S, several authors have reported numerous Neogene localities bearing abundant paleofaunas (some of them from elevations of > 2500 masl) in which xenarthrans are one of the best-represented groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abbreviations: SM = Stratigraphic meter; Lat = latitude; Lon = longitude. Basin Bonini et al (2017a) topologies but their positions are different in the cladograms. Concerning the toxodontinaes from northern South America, the main difference in our result is that the toxodontids recorded in Venezuela (Mixotoxodon, Gyrinodon, and Falcontoxodon) form a monophyletic group (node 45) and belong to a clade that also includes Piauhytherium (node 46; Figure 24a).…”
Section: Toxodontidaementioning
confidence: 95%
“…We performed a maximum parsimony analysis on 28 notoungulate taxa and 59 morphological characters with PAUP* 4.0 (Swofford, 2002). We used the matrix presented by Forasiepi et al (2015) and modified by Bonini et al (2017a). We added Piauhytherium as described by Guérin and Faure (2013), and the new toxodontine from Codore Formation.…”
Section: Toxodontidaementioning
confidence: 99%